Penerapan Kurikulum Anti Bullying Di Smpit Insan Robbani (Studi Living Qur’an) - Adila, Safwa; Hakiki, Kiki Muhamad; Hendro, Beko (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This study aims to describe the application of Qur'an-based character education as an effort to prevent bullying at SMPIT Insan Robbani, and analyze the concept of living Qur'an that is manifested in the program. Using a qualitative case study method with a living Qur'an approach, 9 participants (teachers and students) were involved through observational data collection techniques, semi-structured interviews, and document analysis. The results of the study show that bullying prevention at SMPIT Insan Robbani is carried out through three main programs: Islamic Personal Development (BPI), which specifically instills Qur'anic values, such as the prohibition of insulting (Surah Al-Hujurat: 11), Counseling Guidance (BK), and Islamic Spiritual Extracurricular (Rohis) which plays a role in habituating positive behavior and providing religious-based solutions. Analysis of the living Qur'an identified that the program reflects three forms of Qur'anic reception: Exegesis Reception, in which teachers interpret and instill an understanding of anti-bullying verses; Functional Reception, utilizing the Qur'an as a source of solutions and spiritual guidance in BK services and improving student behavior (according to Surah Yunus: 57); and Socio-Cultural Reception, forming school traditions and culture that reflect family values, harmony, and habituation of positive behavior to prevent violence.